Los artistas del mundo de habla Española - Oviedo-Loredo, Blanca (Kansas State University, 2015)
Students have opportunity to reach learner autonomy and achieve real world applications utilizing communicative competence, a learner centered environment and comprehensible input, incorporated into a unit for student success. The acquisition of language and culture is facilitated in the classroom environment with low affective filters and comprehensible input combining different learning strategies. The activities in this cultural thematic art unit engage student’s interest and activate his or her background knowledge, making meaningful connections with the unit content and their personal lives. Literature, paintings, grammar and vocabulary enable students to build communicative competence in L2. Language learners collaborate and engage in the target language while simultaneously learning about literature, history and culture and learning how artists and writers represent empathy for others as they process words by various Spanish speakers. Additionally, authentic texts and the use of technology enhance students’ linguistic performance. The unit begins with my teaching philosophy followed by a sequence of activities that allow students to process language while they study the consequences of war on those who are affected by it, and a brief section on potential learning outcomes for those who participate in the activities.
Keywords: Comprehensible input; Literature; Communicative competence in L2; Spanish art; Cultura; El uso de videos en la clase; video teaching culture; arte y literatura; Education, Community College (0275); Language, Modern (0291)